2005
DOI: 10.1021/jp046400g
|View full text |Cite
|
Sign up to set email alerts
|

Control of Local Ionization and Charge Transfer in the Bifunctional Molecule 2-Phenylethyl-N,N-dimethylamine Using Rydberg Fingerprint Spectroscopy

Abstract: Local photoionization pathways and charge-transfer dynamics of 2-phenylethyl-N,N-dimethylamine (PENNA) are explored using the recently developed Rydberg fingerprint spectroscopy. PENNA, a molecule that derives its biological significance from its relation to neurotransmitters, has two ionization centers that are separated by an ethyl group. We ionize the molecule in various multiphoton ionization processes using different laser wavelengths. The Rydberg fingerprint spectrum reveals the local nature of the ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 22 publications
1
67
0
Order By: Relevance
“…[5][6][7][8][9] In our research we demonstrated that Rydberg electrons are remarkably sensitive to the geometrical structure of the underlying molecular core. The sensitivity to the molecular structure arises from the phase shift that the Rydberg electron encounters when passing the molecular ion a) rudakovfm@ornl.gov.…”
Section: Introductionmentioning
confidence: 62%
“…[5][6][7][8][9] In our research we demonstrated that Rydberg electrons are remarkably sensitive to the geometrical structure of the underlying molecular core. The sensitivity to the molecular structure arises from the phase shift that the Rydberg electron encounters when passing the molecular ion a) rudakovfm@ornl.gov.…”
Section: Introductionmentioning
confidence: 62%
“…While historically static structure determination methods, such as electron diffraction, have been adapted to fast time scales, there are some limitations, for example, relating to the size of the molecular system [10][11][12][13][14]. Rydberg fingerprint spectroscopy (RFS) takes advantage of the fact that the binding energies of electrons in Rydberg states are sensitive towards the arrangement of atoms in the ion core [15][16][17][18][19]. Because the structure in a Rydberg state most often closely resembles that of the ion state, the spectra of these states feature sharp peaks without vibrational broadening [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a series of studies elucidating the photoionization pathways involving excited valence and Rydberg states, [37][38][39][40][41][42] we employed the two-color three-photon scheme illustrated in Fig. Based on a series of studies elucidating the photoionization pathways involving excited valence and Rydberg states, [37][38][39][40][41][42] we employed the two-color three-photon scheme illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%